Current progress and perspectives of applying cold sintering process to ZrO2-based ceramics. (15th July 2017) - Guo, Hanzheng; Bayer, Thorsten J.M.; Guo, Jing; Baker, Amanda; Randall, Clive A.
Abstract: Zirconia-based ceramics are normally sintered at high temperatures to obtain dense compacts that can deliver good mechanical and/or electrical performance. We recently developed a cold sintering process to achieve dense ceramics at incredibly low temperatures, or an improved densification after a second-step conventional sintering. Here we briefly review the current progress on its relevance to zirconia ceramics as exemplified by yttria-doped zirconia. We will contrast the processing of compositions for a structural-ceramic and an electroceramic. Together with enhanced densification, the processing-structure-property relationship is outlined. The cold sintering technique can provide a cost-effective and energy-saving processing for fabrication of zirconia-based materials. Graphical abstract: